PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DI KANTOR INSPEKTORAT KABUPATEN BADUNG - Merta Darmawan, I Ketut; Mujiati, Ni Wayan (E-Jurnal Manajemen; Vol 6 No 12 (2017), 2017)
ABSTRA CT   This study aims to determine the effect of transformational leadership and organizational commitment to organizational citizenship behavior in Badung district inspectorate. This study was conducted on employees in the inspectorate of Badung Regency. The Population and respondents were 74 employees. The analysis technique used is multiple linear analysis. The results of thi study indicate the transformational leadership has a positive and significant effect on organizational citizenship behavior in inspectorate of Badung regency. The head of the inspectorate of Badung regency must maintain and always pay attention to how much transformational leadership and organizational commitment felt by his subordinates. It aims to create employees who have extra role attitude or organizational citizenship behavior againt other employees at the inspectorate of Badung regency. Keywords : tranformational leadership, organizational commitmen, organizational citizenship behavior